Hydrogen‐Bonding‐Induced Polymorphous Phase Transitions in 2D Organic Nanostructures. Issue 5 (27th February 2013) - Xu, Li; Miao, Xinrui; Zha, Bao; Deng, Wenli
Abstract The 2D self‐assembly of various 2‐hydroxy‐7‐alkoxy‐9‐fluorenone (HAF) molecules has been investigated by scanning tunneling microscopy (STM) at the liquid/solid interface. A systematic study revealed that HAF molecules with different numbers of carbon atoms in their alkoxy chains could form two or three different kinds of nanostructures, that is, less‐ordered, flower‐like, and zig‐zag patterns, owing to the formation of different types of intermolecular hydrogen bonds. The observed structural transition was found to be driven by molecular thermodynamics, surface diffusion, and the voltage pulse that was applied to the STM tip. The zig‐zag pattern was the most stable of these configurations. An odd–even effect on the flower‐like structure, as induced by the odd and even number of carbon atoms in the side chain, was observed by STM. The influence of the odd–even effect on the melting point has a close relationship with the molecular self‐assembled pattern. Our results are significant for understanding the influence of hydrogen‐bonding interactions on the dominant adsorption behavior on the surface and provide a new visual approach for observing the influence of the odd–even effect on the phase transition.